The impact of obesity on semen parameters and hormone levels in infertile men - Erkan Ozdemir; Aytekin Tokmak; Ahmet Deniz Tuzluoglu; Sezen Bozkurt Koseoglu; Mehmet Cinar; Ayse Sahin; Nafiye Yilmaz (Medicine Science, 2016)
Previous studies in overweight men have shown an increased likelihood of abnormal semen parameters. Obesity has been found to be associated with male subfertility. In this study we aimed to investigate the effect of obesity on semen parameters and hormone levels in infertile males. This was a prospective cross-sectional study designed to assess the influence of obesity on semen parameters and hormone levels in infertile men. 88 obese [Body mass index (BMI) ≥30 kg/m2] men and 169 non-obese (BMI [Med-Science 2016; 5(3.000): 780-4]